2005
DOI: 10.2116/analsci.21.783
|View full text |Cite
|
Sign up to set email alerts
|

X-ray Absorption Spectral Analysis with a 9 V Battery X-ray Generator

Abstract: The measurements of X-ray absorption spectra (XAS) and Xray absorption fine structure (XAFS) have usually been performed by using a synchrotron radiation facility. It is widely believed that high intensity and monochromatized X-rays are necessary for XAS and XAFS experiments. In the present paper, however, we report K-edge XAS measurements of Ca contained in paper sheets using a dry electric battery XAS spectrometer.As one of the smaller X-ray sources, X-ray emission using the charging phenomenon of an insulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…Radioisotopes, small air-cooled X-ray tubes, or pyroelectric X-ray emitters are used. [11][12][13][14][15][16][17][18][19] Terasawa found that the charge-up of an insulator produced X-rays. 20 He invented an X-ray device, as shown in Fig.…”
mentioning
confidence: 99%
“…Radioisotopes, small air-cooled X-ray tubes, or pyroelectric X-ray emitters are used. [11][12][13][14][15][16][17][18][19] Terasawa found that the charge-up of an insulator produced X-rays. 20 He invented an X-ray device, as shown in Fig.…”
mentioning
confidence: 99%
“…[6] The target was Cu, C, and Ni. The experiment was easy routine work as the usual SEM measurement but the beam was fixed at an area and EDX was measured.…”
Section: Methodsmentioning
confidence: 99%
“…Experimental geometry to measure X-ray absorption spectra (Reproduced from Ref. [13] ) by permission from the Japan Society for Analytical Chemistry.…”
Section: Samplementioning
confidence: 99%
“…The sensitivity difference in transition metals, [10] environmental, [11] and rice analyses [12] has been reported after the publication of Ref. [9] .The authors have also used the pyroelectric X-ray generator for the X-ray absorption spectrometry using an Si-PIN detector [13] and a superconducting energy dispersive X-ray detector. [14] The geometry to measure the X-ray absorption spectra is shown in Fig.…”
mentioning
confidence: 99%